IDENTIFIKASI DAN RENCANA PENGEMBANGAN KAWASAN WISATA BUDAYA KORIDOR SUNGAI KAPUAS - KOTA PONTIANAK - Fadiah Umar; Siti Nurisjah; Ricky Avenzora (Jurnal Lanskap Indonesia, 2010)
Kapuas river which run in the middle of the city of Pontianak, known as the longest river in Indonesia, having economic function significantly, and also as the beginning site of Malay culture at Pontianak. However, developing urban economic aspect are mostly neglect cultural as well ecological aspects on that riparian. The study objectives are to develope Kapuas River Corridor as tourism area, mainly as local cultural tourism activities. Scoring and spatial methods were develop to analyzed cultural, economic and physical aspect of the sites. 133,4 Ha was deliniated as cultural tourictic area. East Pontianak, which beginning site of Malay culture in city Pontianak, has the highest cultural values and was planning the center of main cultural tourism. Interpretation cultural tourism paths was design to explain cultural message of the planned area. To conserve the local cultural touristic area, some integrated programs are developed to increase public and local goverment participation.